Thai Undergraduate Student Awareness of Regular and Irregular Grapheme-Phoneme Correspondence - Perrodin, David D. (Institut Agama Islam Negeri Kudus, 2021)
Recent events in Thailand in reference to the teaching of phonics for better comprehension of English vocabulary have highlighted the overuse of identifying letter-sound relationships in English by utilizing the familiar Thai orthography to assist developing Thai EFL learners. This paper investigated the long-term effects of using such pedagogy on recognizing regular and irregular Grapheme-Phoneme Correspondences (GPC) in English by Thai undergraduate students. To address this matter, the study used a convenience sampling of 373 first-year university students from 11 general education English classes at a mid-sized private university near Bangkok, Thailand. The familiar English poem I Take It You Already Know was employed for data collection, for it consists of a practical ratio of frequent and infrequent English grapheme-phoneme correspondences. Extensive lists of recognized grapheme-phoneme correspondences were used to identify the frequent or regular, and the infrequent or irregular main phoneme present in each of the 60 most frequently queried content words of the poem. Point-Biserial Correlation was employed to measure the strength of association between the frequency occurrence of the most queried content words from the data set, and the examined weighted word frequency data. The findings suggest that, in general, the Thai undergraduate students demonstrated an overall lack of recognition of regular and irregular Grapheme-Phoneme Correspondences of English.